مصادر الخبر في الصحافة الالكترونية - جنان هبة الله شمة; فدوى عطلي; د/ رقية لقلوق (جامعة عمار ثليجي الاغواط, 2025)
ملخص الدراسة يهدف هذا البحث إلى دراسة وتحليل مصادر الخبر في الصحافة الإلكترونية، من خلال نموذج تطبيقي يتمثل في صحيفة الخبر الجزائرية، باعتبارها من أبرز الصحف الرقمية في الساحة الإعلامية الوطنية. وقد تم التركيز على تصنيف المصادر المعتمدة في إنتاج الخبر، ومدى توازن الصحيفة بين المصادر التقليدية (كالبيانات الرسمية والمراسلين) والمصادر الحديثة (مثل مواقع التواصل الاجتماعي وشهود العيان) المصادر الداخلية والخارجية. وقد تم الإعتماد على المنهج الوصفي بأسلوب تحليلي على عينة بلغت 73 خبر للثلاثي الأول لسنة 2025(جانفي، فيفري، مارس) حيث تم إختيار هذه العينة عن طريق الأسبوع الإصطناعي باستخدام آداة الملاحظة وآداة تحليل المضمون. أظهرت نتائج التحليل أن الصحيفة تعتمد على التنوع في مصادرها، إلا أن ذلك التنوع يرافقه تفاوت في درجة التحقق والمصداقية، خاصة عند الاعتماد على مصادر غير رسمية. كما أبرزت الدراسة أهمية وضع سياسات تحريرية واضحة في التعامل مع المصادر، وتوصي بتعزيز التكوين الصحفي في مجال التحقق الرقمي والاعتماد على مصادر موثوقة للحفاظ على مهنية العمل الصحفي في البيئة الرقمية. الكلمات المفتاحية:الصحافة الإلكترونية، مصادر الخبر، صحيفة الخبر الإلكترونية الجزائرية ، الإعلام الرقمي.   Abstract: This research aims to study and analyze news sources in electronic journalism, through an applied model represented by the Algerian newspaper Al-Khabar, as it Is one of the most prominent digital newspaper’s in the national media aréna،The focus was on classifying the sources relied upon in producing news, and the extent of the newspaper's balance between traditional sources (such as official statements and correspondants) and modern sources (such as social networking sites and eyewitnesses). Internal and external sources The descriptive approach was relied upon with an analytical method on a sample of 73 news items for the first quarter of 2025 (January, February, and March). This sample was selected through the artificial week using the observation tool and the content analysis tool. The results of the analysis showed that the newspaper relies on diversity in its sources, but that this diversity is accompanied by a difference in the degree of verification and credibility, especially when relying on unofficial sources. The study also highlighted the importance of establishing clear editorial policies in dealing with sources, and recommends strengthening journalistic training in the field of digital verification and relying on reliable sources to maintain the professionalism of journalistic work in the digital environment. Keywords:Electronic journalism, news sources, electronic criminal newspaper Al-Khabar.Digital media.
دراسة وصفية تحليلية لصحيفة الخبر الالكترونية الجزائرية